Excavation of a unique sailboat at Kadakkarappally, Kerala - M. V. Nair, V. Selvakumar, and P. K. Gopi (CURRENT SCIENCE, VOL. 86, NO. 5, 10 MARCH 2004, 2004)
Recent archaeological excavations at Kadakkarappally, Kerala have exposed an interesting sailboat in a partly intact condition. The method of construction adopted in the boat, which has no known parallels, and the wellpreserved condition of the wood, considering the hostile environmental conditions prevailing in India, make this a unique find. The preliminary findings of the excavations are presented here.